2018
DOI: 10.1002/cpt.1111
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, First‐in‐Human, Healthy Volunteer Trial of sutimlimab, a Humanized Antibody for the Specific Inhibition of the Classical Complement Pathway

Abstract: Aberrant activation of the classical complement pathway is the common underlying pathophysiology of orphan diseases such as bullous pemphigoid, antibody‐mediated rejection of organ transplants, cold agglutinin disease, and warm autoimmune hemolytic anemia. Therapeutic options for these complement‐mediated disorders are limited and sutimlimab, a humanized monoclonal antibody directed against complement factor C1s, may be potentially useful for inhibition of the classical complement pathway. A phase I, first‐in‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 19 publications
2
63
1
Order By: Relevance
“…In the nonhuman primate toxicology studies, no signs of arrhythmias were observed in electrocardiographic evaluations and no adverse cardiovascular findings were noted after up to 26 weeks of BIVV009 administration at 180 mg/kg/week (data not shown). In addition, no cardiac toxicity was observed in any of the other participants dosed in the phase 1 study (48 healthy volunteers [Bartko et al, 2018;Mü hlbacher et al, 2017], 10 kidney transplant recipients [Eskandary et al, 2018 ], 10 patients with cold agglutinin disease [Jäger et al, 2019], and 9 patients with BP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nonhuman primate toxicology studies, no signs of arrhythmias were observed in electrocardiographic evaluations and no adverse cardiovascular findings were noted after up to 26 weeks of BIVV009 administration at 180 mg/kg/week (data not shown). In addition, no cardiac toxicity was observed in any of the other participants dosed in the phase 1 study (48 healthy volunteers [Bartko et al, 2018;Mü hlbacher et al, 2017], 10 kidney transplant recipients [Eskandary et al, 2018 ], 10 patients with cold agglutinin disease [Jäger et al, 2019], and 9 patients with BP).…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether complement activation and IgG deposition were BIVV009-dependent, post-washout biopsies from 4 patients (three of whom had showed a decrease in C3c and IgG staining in their on-treatment biopsy compared with their pretreatment biopsy) were collected at least 28 days after the last infusion. Based on studies in healthy volunteers, it was estimated that this timeframe would allow for complete recovery of classical pathway activity as measured by CH50 (Bartko et al, 2018). In 3 of these 4 patients (001, 005, 008), deposition of C3c and IgG along the dermal-epidermal junction that had been partially or completely absent while under BIVV009 reappeared in the post-washout biopsies, when serum CH50 activity was restored to pretreatment levels ( Figure 2).…”
Section: Effect Of Targeting C1s In Bullous Pemphigoidmentioning
confidence: 99%
“…A phase I, double-blind, randomized, placebo-controlled, dose-escalation trial of single and multiple doses of sutimlimab versus placebo has been conducted 186 , followed by two phase Ib trials. In one of these phase Ib trials, the effect of sutimlimab in haemolytic anaemia associated with cold agglutinin disease was assessed; all six patients who received sutimlimab no longer needed blood transfusions 187 .…”
Section: Complement-targeted Therapiesmentioning
confidence: 99%
“…Sutimlimab (previously known as TNT009 or BIVV009) is a humanized monoclonal antibody against C1s. 79 An in vitro study of TNT003, the murine antibody from which sutimlimab is derived, found complete inhibition of complement activation, C3 deposition, and phagocytosis of erythrocytes in the presence of patient sera as a source of CA and normal human serum as a source of complement. 19 In a recent clinical Phase IB trial describing 10 patients with CAD, weekly intravenous administration of sutimlimab increased Hb levels by a median of 1.6 g/dL within the first week of treatment and by 3.9 g/dL within 6 weeks.…”
Section: Complement-directed Therapiesmentioning
confidence: 99%